ANTITHROMBOTIC THERAPY AT PERCUTANEOUS CORONARY INTERVENTIONS - V. A. Sulimov (Рациональная фармакотерапия в кардиологии, 2016)
Possibilities of modern antiplatelet and antithrombotic therapy at percutaneous coronary interventions in patients with coronary artery disease are surveyed. Data of multicenter randomized clinical trials and meta-analyses are discussed. Possibilities of various drugs at percutaneous coronary interventions are reported from position of the international clinical guidelines.